A Phenomenological Investigation of Doctoral Students’ Gatekeeping Experiences - Shawna M. Corley; Jessica Lloyd-Hazlett; Hope Schuermann; Noel Blessing (Teaching and Supervision in Counseling, 2020)
Counselor education doctoral students serve as gatekeepers simultaneous to their own training and evaluation. We used transcendental phenomenology to examine the gatekeeping experiences of 15 doctoral students at three programmatic levels. Findings and implications related to two primary themes, (a) precarious positions and power and (b) developing a gatekeeper identity, are discussed.
Keywords: gatekeeping; counselor education; doctoral students; supervision